Molecular Transducers from Roots Are Triggered in Arabidopsis Leaves by Root-Knot Nematodes for Successful Feeding Site Formation: A Conserved Post-Embryogenic De novo Organogenesis Program? - Olmo, Rocío; Cabrera, Javier; Moreno-Risueno, Miguel A.; Fukaki, Hidehiro; Fenoll, Carmen; Escobar, Carolina (Frontiers in Plant Science, 2017)
Root-knot nematodes (RKNs; Meloidogyne spp.) induce feeding cells (giant cells; GCs) inside a pseudo-organ (gall) from still unknown root cells. Understanding GCs ontogeny is essential to the basic knowledge of RKN-plant interaction and to discover novel and effective control strategies. Hence, we report for the first time in a model plant, Arabidopsis, molecular and cellular features concerning ectopic de novo organogenesis of RKNs GCs in leaves. RKNs induce GCs in leaves with irregular shape, a reticulated cytosol and fragmented vacuoles as GCs from roots. Leaf cells around the nematode enter G2-M shown by ProCycB1;1:CycB1;1(NT)-GUS expression, consistent to multinucleated GCs. In addition, GCs nuclei present irregular and varied sizes. All these characteristics mentioned, being equivalent to GCs in root-galls. RKNs complete their life cycle forming a gall/callus-like structure in the leaf vascular tissues resembling auxin-induced callus with an auxin-response maxima, indicated by high expression of DR5::GUS that is dependent on leaf auxin-transport. Notably, induction of leaves calli/ GCs requires molecular components from roots crucial for lateral roots (LRs), auxin-induced callus and root-gall formation, i.e. LBD16. Hence, LBD16 is a xylem pole pericycle specific and local marker in LR primordia unexpectedly induced locally in the vascular tissue of leaves after RKN infection. LBD16 is also fundamental for feeding site formation as RKNs could not stablish in 35S::LBD16-SRDX leaves, and likely it is also a conserved molecular hub between biotic and developmental signals in Arabidopsis either in roots or leaves. Moreover, RKNs induce the ectopic development of roots from leaf and root-galls, also formed in mutants compromised in LR formation, arf7/arf19, slr and alf4. Therefore, nematodes must target molecular signatures to induce post-embryogenic de novo organogenesis through the LBD16 callus formation pathway partially different from those prevalent during normal LR development.